The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1007/bf00210281
|View full text |Cite
|
Sign up to set email alerts
|

Prognostisch relevante Faktoren bei der intraabdominalen infektion

Abstract: From 1.1.1982-30.9.1989 280 patients were treated for intraabdominal infection at the clinic for general and abdominal surgery. With regard to their prognostic significance, the extent and localization of the peritonitis, abscess formation, the number of failed organ system, patients' age, total protein, thrombocytes and leucocytes were examined in these patients. The most unfavorable prognosis showed diffuse peritonitis with a mortality rate of 47.2%. Subsequent abscessing worsened the prognosis of the illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Wahl and associates have rated diffuse peritonitis with mortality of 47%, a most unfavorable factor 4 . Ten to fifteen percent of patients may need re-exploration for persistent or recurring sepsis and mortality in this group is considerable 2,8,9,24,34 The significance of the septic focus was highlighted by Bohnen who showed that colonic perforation is high risk while appendix perforations has good recovery rate 3 .…”
Section: Other Prognostic Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wahl and associates have rated diffuse peritonitis with mortality of 47%, a most unfavorable factor 4 . Ten to fifteen percent of patients may need re-exploration for persistent or recurring sepsis and mortality in this group is considerable 2,8,9,24,34 The significance of the septic focus was highlighted by Bohnen who showed that colonic perforation is high risk while appendix perforations has good recovery rate 3 .…”
Section: Other Prognostic Indicatorsmentioning
confidence: 99%
“…It consists of a spectrum of pathologies namely, primary, secondary and tertiary peritonitis and, intraabdominal abscess. In spite of innovations in operative and antimicrobial therapy, and intensive care, mortalities of 5-40% are being reported [1][2][3][4][5][6][7][8][9] . In our environment., peritonitis is a common cause of nontraumatic death in emergency unit with the scourge of typhoid perforation, late presentations of appendicitis and strangulated bowel being the key reasons [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Wahl et al showed 47% mortality in diffuse peritonitis patients and according to him these group need relaparotomy for persistent recurring infection. 36 In this study, Colonic origin cases had 42.85% mortality while non-colonic origin cases had 25.8% mortality so this study showed that presence of colonic origin is an important variable for adverse outcome. This finding is similar with study of Bohnen et al and contrast with study by Linder et al 25,37 The mortality rate in patients with clear exudate was 0.0%, purulent exudate was 20 % while in faecal exudate the mortality was 68% this was statistically significant (p<0.05) and hence presence of faecal exudate is an important variable for adverse outcome.…”
Section: Discussionmentioning
confidence: 55%
“…There were many studies mentioned that faecal exudate is an important variable for outcome of patients. 13,16,36,38 This study showed that there was no death in patients with MPI score less than 21, in MPI score between 21 to 29 the mortality was 20%, while in patients with MPI score greater than 29 the mortality was 95.65%. Mean MPI of Discharged patients was 17.97±5.255 compared to 33.22±5.018 among declared patients.…”
Section: Discussionmentioning
confidence: 83%
“…Organ failure is an important parameter for most scoring systems [18,23,24]. Most authors agree that patients with at least one organ failure before relaparotomy have a higher mortality rate.…”
Section: Discussionmentioning
confidence: 99%